2007
DOI: 10.1097/dbp.0b013e3180327b55
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Incidence of Publicly Reported Shaken Baby Syndrome Cases: Is Crying a Trigger for Shaking?

Abstract: : The findings provide convergent indirect evidence that crying, especially in the first 4 months of age, is an important stimulus for SBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(101 citation statements)
references
References 33 publications
6
89
1
4
Order By: Relevance
“…O padrão de choro do bebê nos primeiros meses de vida inclui ainda episódios de choro prolongado, inconsolável e imprevisível, que ocorrem normalmente no final da tarde ou início da noite e são acompanhados por expressões faciais de dor e aumento do tônus muscular (Barr et al, 2006;Lee et al, 2007).…”
Section: Nrl Lopes and Lca Williamsunclassified
See 2 more Smart Citations
“…O padrão de choro do bebê nos primeiros meses de vida inclui ainda episódios de choro prolongado, inconsolável e imprevisível, que ocorrem normalmente no final da tarde ou início da noite e são acompanhados por expressões faciais de dor e aumento do tônus muscular (Barr et al, 2006;Lee et al, 2007).…”
Section: Nrl Lopes and Lca Williamsunclassified
“…Esses dados indicam um bom conhecimento dos participantes sobre o padrão de choro do bebê. Cabe destacar, entretanto, que o item "Bebês choram sem motivo" deveria ser alterado para "Bebês choram sem uma razão aparente", de modo a se aproximar com o proposto na literatura da área, que aponta a ocorrência de episódios de choro inconsolável e sem razão aparente (Barr et al, 2005;Barr et al, 2006;Lee et al, 2007 Nash et al (2008), essa percepção de intencionalidade do comportamento do bebê pode decorrer de uma interpretação inadequada dos pais sobre o fato de os bebês se acalmarem após ganharem a atenção dos pais em resposta ao seu choro. Esses autores ressaltam, entretanto, que é preciso cautela com essa percepção dos pais acerca do choro do bebê, visto que, em alguns casos, acreditar que um bebê chore apenas para ganhar atenção pode gerar sentimentos de ressentimento e frustração, aumentando o risco para ocorrência de maustratos, especialmente o TCV.…”
Section: Tabela 2 Porcentagens De Resposta Para Cada Item Do Questionunclassified
See 1 more Smart Citation
“…Shaking an infant younger than 2 years of age results in often-fatal brain injury plus a plethora of secondary injuries caused by gripping the infant during violent shaking (broken ribs, and bruising on the torso and extremities, plus retinal tears and bleeding in the eye; Jentzen, 2001). Research on the perpetration of SBS has identified only one consistent predictor -an infant's inconsolable cry (Lee & Barr, 2007;Barr, Trent, & Cross, 2006).…”
Section: Acute Risk For the Mutually Dysregulated Dyadmentioning
confidence: 99%
“…That the incidence of abusive head trauma parallels this normal developmental crying curve may serve as additional corroboration of the association between crying and abuse. 15,16 The severity and frequency of caregivers' adverse responses to crying have largely been underappreciated. In 1 study, almost 6% of parents of 6-month-old infants admitted that they had smothered, slapped, or shaken their infant at least once because of his or her crying.…”
Section: Triggersmentioning
confidence: 99%